Investigating the potential of avocado seeds for bioethanol production: A study on boiled water delignification pretreatment - Herliati Rahman; Ayu Nehemia; Hadiatun Puji Astuti (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
The increasing need for alternative fuels to replace fossil fuels has made bioethanol a promising option. Although numerous sources of sugar generation and agricultural wastes can be converted into ethanol, Avocado Seeds (AS) are particularly attractive as raw materials due to their abundance, high carbohydrate content, and lack of interactions with the food chain. Therefore, this study investigated the potential of AS for bioethanol production using several steps, including boiled water delignification pretreatment, catalytic hydrolysis, and fermentation with Saccharomyces cerevisiae. The delignification pretreatment of AS involved soaking in 4% (w/v) sodium hydroxide liquor for 24 hours. Then the mixture was heated to 80°C and stirred slowly for 2.5 hours and after that washing with boiled water at 100 oC for 1.5 hours and screening the mixture. Subsequently, catalytic hydrolysis and fermentation were carried out using two different concentrations of Saccharomyces cerevisiae as yeast, namely 10% (w/v) and 15% (w/v). Qualitative sample analysis was conducted using scanning electron microscopy (SEM) to observe the effect of delignification pretreatment, while FTIR analysis using Thermo Scientific Nicolet iS50 was used to test for glucose functional groups. Quantitative analysis was performed using gas chromatography 7890b mass spectrophotometry 5977A, Agilent DBVRX to determine hydrolysate fermentation. The results revealed that the highest ethanol yield was achieved through fermentation with 15% (w/v) yeast and 40% (v/v) catalyst, resulting in an ethanol yield of 83.755% of the theoretical maximum.